The Transition from Face-to-Face to Remote Mode: Experience of University Professors in the Pandemic Context - Galbán Lozano, Sara Elvira (2022)
The objective of this investigation is to acknowledge the experience of university professors during the COVID-19 contingency by following their transition from a face-to-face to a distant teaching modality. To do this, we started from the naturalistic paradigm, the qualitative approach, and the phenomenological method, considering the narrative and the teacher evaluation for the data collection. The participants in this study were 24 pedagogy professors from a private university in Mexico City. One of the main findings in the transition from face-to-face to distant modality was the importance of institutional support and organizational culture. The other one is related to change management and commitment to the educational process for both teachers and students. In addition to planning flexibility and student learning, as the center of teaching activity, personal interaction can be favored through teaching strategies that promote participation and that are supported by technology.